2010
DOI: 10.1002/ps.2048
|View full text |Cite
|
Sign up to set email alerts
|

Ingested RNA interference for managing the populations of the Colorado potato beetle, Leptinotarsa decemlineata

Abstract: These results suggest that the efficient induction of RNAi using bacteria to deliver dsRNA is a possible method for management of CPB. This could be also a promising bioassay approach for genome-wide screens to identify effective target genes for use as novel RNAi-based insecticides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
295
1
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(317 citation statements)
references
References 26 publications
(45 reference statements)
14
295
1
7
Order By: Relevance
“…RNAi mediated by dsRNA ingestion requires higher dosage and multiple administrations until the onset of silencing in insects when compared to RNAi via injection in the haemolymph (Chen et al, 2008;Tian et al, 2009;Zhu et al, 2011), although dosages needed to elicit effect via injection in H. armigera remain measured in micrograms (Bober and Rafaeli, 2010;Cai et al, 2014;Du et al, 2012;Hou et al, 2012;Qiao et al, 2014;Sivakumar et al, 2007;Tang et al, 2012;Wang et al, 2010;Yang and Han, 2014a).…”
Section: Nucleotide Dsrna Concentrationmentioning
confidence: 99%
“…RNAi mediated by dsRNA ingestion requires higher dosage and multiple administrations until the onset of silencing in insects when compared to RNAi via injection in the haemolymph (Chen et al, 2008;Tian et al, 2009;Zhu et al, 2011), although dosages needed to elicit effect via injection in H. armigera remain measured in micrograms (Bober and Rafaeli, 2010;Cai et al, 2014;Du et al, 2012;Hou et al, 2012;Qiao et al, 2014;Sivakumar et al, 2007;Tang et al, 2012;Wang et al, 2010;Yang and Han, 2014a).…”
Section: Nucleotide Dsrna Concentrationmentioning
confidence: 99%
“…It is obvious that the RNAi technology, allowing for in vivo post-transcriptional silencing of essential genes, thereby causing mortality with little effect on non-target species, gained significant interest in pest management research over the past years Zhang et al, 2013). Indeed, several studies have demonstrated that this technique shows great potential for the development of novel biological strategies for selectively controlling agricultural pests (Baum et al, 2007;Zhu et al, 2011). Nevertheless, an important aspect in exploiting the RNAi response remains the introduction of dsRNA in the cells, and while the intracellular mechanisms appear highly conserved, the degree of sensitivity towards RNAi varies strongly among insects, with many (economically important) species being refractory to environmentally delivered dsRNA (Scott et al, 2013;Swevers et al, 2013b;Wynant et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by the ability to quickly develop resistance to a wide range of chemical pesticides, urging the need to develop alternative management strategies (Zhu et al, 2011). Several studies have shown that CPB is able to take up dsRNA from the gut lumen and subsequently induce a potent systemic RNAi response, suggesting that RNAi could be a feasible novel control method for this insect pest (Cappelle et al, 2016;Zhu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…housekeeping genes), genes with high mRNA turnover coding for proteins with short half-life, stability of dsRNA, and the ability to deliver sufficient amounts of dsRNA (Huvenne and Smagghe, 2010;Scott et al, 2013). The potential applications for RNAi in pest management include oral administration of dsRNA in baits (Zhou et al, 2008), embedded in nanoparticles (Zhang et al, 2010), expressed in E. coli and formulated as a biological insecticide (Zhu et al, 2011), or expressed in transgenic plants (Baum et al, 2007;Mao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%